Cloud Computing Research (2010–2026): A Scopus-Based Bibliometric Analysis of Intellectual Structure and Topic Shifts - Loso Judijanto; Rizki Dewantara (Westscience Press, 2026)
The research aims at mapping the evolution of cloud computing studies from 2010 to 2026 through the analysis of academic literature using bibliometrics. This approach will provide information on the structure of the knowledge, major contributions, and the thematic trends within the area. In the present work, the bibliometric analysis is based on Scopus indexation. The research uses several types of analysis: co-authorship, citation, and keyword co-occurrence analyses. VOSviewer was chosen as the main bibliographic software for data mining. The analysis shows that the field is dominated by major researchers representing countries including the USA, China, and India, which indicates a partially fragmented cooperation among experts in the domain. Bibliometric analysis through citation shows that research papers in cloud computing architecture, Internet of things, and edge computing play a crucial role, as they set the basis of the topic and show the trend toward decentralization and integration in computing. In addition, the multidimensionality of research in cloud computing was analyzed through keywords, which revealed not only technical issues but also security, applications, green computing, and energy efficiency. This study contributes to the literature by providing a systematic overview of the development and current landscape of cloud computing research, offering valuable insights for researchers and practitioners in identifying future research directions and opportunities for interdisciplinary collaboration.